Effectiveness of Eco Enzyme-Based Biochar Application on Increasing Post-Flood Soil Fertility on Agricultural Land - Hamela Sari Sitompul; Octasella Ainani As’ad; Nurhadida Nasution; Supriadi Surbakti (Journal of Agriculture, 2026)
Post-flood land rehabilitation efforts are needed to restore soil productivity sustainably, one of which is through the use of eco-enzyme-based biochar. This study aims to analyse the effectiveness of eco-enzyme-based biochar application in increasing post-flood soil fertility on agricultural land in Gampong Tupah, Karang Baru District, Aceh Tamiang Regency. The study used a field experiment method with a non-factorial Randomised Block Design (RBD) consisting of five treatment levels, namely P0 (control), P1, P2, P3, and P4. The parameters observed included chemical, physical, and biological properties of the soil. The results showed that the application of eco-enzyme-based biochar increased soil pH, organic carbon, total nitrogen, available phosphorus, available potassium, cation exchange capacity, total porosity, and soil microorganism populations, while also reducing bulk density. The results showed that the P4 treatment, soil pH from 4.82 to 6.21, organic C from 1.26% to 3.08%, total N from 0.15% to 0.32%, available P from 8.15 to 23.91 ppm, CEC from 13.84 to 28.84 cmol(+) kg?¹, total porosity from 42.18% to 56.45%, and soil microorganism population from 2.10 × 10? to 10.14 × 10? CFU g?¹, accompanied by a decrease in bulk density from 1.47 to 1.16 g cm?³ compared to the control.